Improved electrical ideality and photoresponse in near-infrared phototransistors realized by bulk heterojunction channels - Ning Li; Yanlian Lei; Yanqin Miao; Furong Zhu (iScience, 2022)
Summary: The factors that affect the electrical ideality and photoresponse in near-infrared (NIR) organic phototransistors (OPTs) are still nebulous. Here, simultaneous increase in electrical ideality and NIR response in the OPTs is realized by applying a bulk heterojunction (BHJ) channel. The acceptor in the channel helps to trap the undesirable injected electrons, avoiding the accumulation of the electrons at the active channel/dielectric interface, and thereby improving the hole transporting. Use of a BHJ channel also helps reducing the contact resistance in the OPTs. The electrical stability is then improved with mitigated dependence of charge mobility on gate voltage in the saturation region. The BHJ channel also offers an improved photoresponse through enhanced exciton dissociation, leading to more than one order of magnitude increase in responsivity than that in a control OPT. The results are encouraging, which pave the way for the development of high-performing NIR OPTs.